MXene-based hydrogel material with directional pore structure, preparation method and application thereof

By introducing a directional pore structure into the MXene-based hydrogel material, combining the conductivity of MXene and the polarization loss of water, the problem of insufficient mechanical properties of the existing MXene-based porous materials is solved, and the ultra-flexibility, stretchability and excellent electromagnetic shielding performance of the material are achieved.

CN115651219BInactive Publication Date: 2025-04-01SHANDONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211078057.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-05
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing MXene-based porous materials have shortcomings in mechanical properties and stretchability, which limits their use in applications such as flexible electronic devices.

Method used

By uniformly dispersing the MXene aqueous dispersion with the water-soluble polymer solution, and after directed freezing in a cold source, and salting out treatment was performed, MXene-based hydrogel material with a directional pore structure was prepared.

Benefits of technology

The prepared MXene-based hydrogel material has excellent electromagnetic shielding and electromechanical sensing properties, excellent mechanical properties, ultra-flexible and stretchable, and is suitable for applications such as flexible electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115651219B_ABST
    Figure CN115651219B_ABST
Patent Text Reader

Abstract

The present invention relates to a MXene-based hydrogel material with a directional pore structure, and a preparation method and application thereof. The preparation method comprises the following steps: (1) mixing a MXene aqueous dispersion with a water-soluble polymer solution, and dispersing them uniformly to obtain a mixed aqueous dispersion; (2) pouring the mixed aqueous dispersion obtained in step (1) into a mold, and placing it in a cold source for freezing treatment; (3) placing the frozen product obtained in step (2) into a salt solution, performing salting-out treatment, and washing to obtain a MXene-based hydrogel material with a directional pore structure. The MXene-based hydrogel material has a directional internal pore structure, excellent mechanical properties, ultra-flexibility and stretchability, and excellent electromagnetic shielding performance and motion detection performance. The preparation method is simple, and the production energy consumption and cost are low, and large-scale industrial applications can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nanomaterials, and specifically relates to a preparation method and application of a MXene-based hydrogel material with a directional pore structure. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Transition metal carbide MXene is a novel two-dimensional inorganic compound composed of transition metal carbides with a thickness of several atomic layers. Films or 3D porous foams / aerogels constructed with MXene as the matrix have excellent electromagnetic shielding performance. Compared with thin film materials, the introduction of porous structures in shielding materials can enhance the multiple reflections of electromagnetic waves, improve the absorption of incident electromagnetic waves by shielding materials, and improve the shielding performance of materials. In addition, by designing the internal pore structure of porous materials to form a directional honeycomb channel structure, the multiple reflections of incident electromagnetic waves can be further enhanced, and the shielding ability of materials can be improved. In practical applications, materials must not only have high electromagnetic interference shielding performance, but also have good mechanical strength, flexibility and stretchability, which is very important for some flexible electronic devices. Although porous materials such as foams / aerogels have excellent shielding performance, their mechanical strength is low, their flexibility is general, and especially their stretchability is poor, which limits their application in flexible electronics such as wearables.

[0004] Hydrogel is a porous material composed of a cross-linked polymer skeleton and water-rich pores. It has excellent flexibility, elasticity, and fatigue resistance, especially excellent stretchability. It is expected to replace porous foam / aerogel and become a new generation of electromagnetic shielding materials. At the same time, the water contained in the hydrogel pore structure will be strongly polarized under an external electromagnetic field, greatly losing the energy of the incident electromagnetic wave. Due to the excellent hydrophilicity of MXene, MXene conductive materials can be evenly dispersed in the hydrogel to form a three-dimensional conductive network, enhance the conductivity loss of the material, and cause the incident electromagnetic wave to be strongly reflected. However, for most hydrogel materials, due to the low mechanical strength of the pore wall inside, its porous structure is very easy to deform, and it is difficult to design a directional and orderly pore structure inside, which hinders the further improvement of the shielding effectiveness of the hydrogel material. Therefore, the development and preparation of hydrogels with directional pore structures is of great significance in practical applications. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a MXene-based hydrogel material with a directional pore structure, a preparation method thereof, and an application thereof. The MXene-based hydrogel material with a directional pore structure has an internal pore structure with directional arrangement, excellent mechanical properties, ultra-flexibility and stretchability, and excellent electromagnetic shielding performance and electromechanical sensing performance. The preparation method is simple, and the production energy consumption and cost are low, so large-scale industrial applications can be realized.

[0006] Specifically, the technical solution of the present invention is as follows:

[0007] In a first aspect, the present invention provides a method for preparing a MXene-based hydrogel material having a directional pore structure, which comprises the following steps:

[0008] (1) uniformly dispersing the MXene aqueous dispersion and the water-soluble polymer solution to obtain a mixed aqueous dispersion;

[0009] (2) pouring the mixed aqueous dispersion obtained in step (1) into a mold and placing it in a cold source for directional freezing;

[0010] (3) The product obtained in step (2) is placed in a salt solution for salting out, and after washing, a MXene-based hydrogel material having a directional pore structure is obtained.

[0011] The MXene-based hydrogel material with a directional pore structure provided by the present invention fully combines the excellent electrical conductivity of MXene itself, the strong polarization loss of water, and the internal directional pore structure and other properties, so that the MXene-based hydrogel material with a directional pore structure has excellent electromagnetic shielding performance and sensitive electromechanical sensing function.

[0012] During the directional freezing process, ice crystals grow in a directional manner along the temperature gradient. Under the extrusion of ice crystals, MXene and polymer chains are tightly stacked, and water molecules are squeezed out to form a continuous pore wall with a high solid content. During the salting-out treatment process, the ice crystals melt, and a large number of hydrogen bonds are formed between the tightly stacked MXene and the hydroxyl groups on the surface of the polymer chains. The strong physical cross-linking significantly improves the mechanical properties of the pore wall and enhances the pore wall strength, so that the directional pore structure produced after the melting of the ice crystals is retained, and the structure is stable and not easily deformed, and finally a stable directional pore structure is formed inside the MXene-based hydrogel.

[0013] The MXene is a two-dimensional transition metal carbide, nitride or carbonitride. Preferably, the MXene is titanium carbide Ti 3 C 2 .

[0014] The water-soluble polymer includes any one or a combination of at least two of cellulose, hydroxymethyl cellulose, carboxymethyl cellulose, lignin, starch, hydroxymethyl starch, acetic starch, vegetable glue, animal glue, polyacrylamide, polyvinyl pyrrolidone, polyurethane, polyacrylic acid, polyacrylate, polyvinyl alcohol (PVA), polyaniline, polylactic acid, polymaleic anhydride or polyethylene glycol, more preferably polyvinyl alcohol.

[0015] In step (1), based on the mixed aqueous dispersion, the mass percentage content of MXene is 0.1-10%, for example, it can be 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, and specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0016] Based on the mixed aqueous dispersion, the mass percentage of the polymer is 0.1% to 10%, for example, it can be 0.1%, 0.2%, 0.5%, 0.8%, 1%, 3%, 5%, 8%, 10%, and specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0017] Preferably, the mold is a polytetrafluoroethylene mold with a metal bottom.

[0018] Preferably, the freezing treatment temperature is -196 to -20°C, more preferably -196°C.

[0019] Preferably, the cold source is one of liquid nitrogen, a low-temperature refrigerator, dry ice, and an ethanol / liquid nitrogen bath.

[0020] Preferably, the salt includes any one or a combination of at least two of sodium chloride, calcium chloride, copper chloride, sodium citrate, sodium sulfate, sodium nitrate, sodium acetate, potassium sulfate, potassium carbonate, and potassium chloride, and more preferably any one or a combination of at least two of sodium chloride, sodium citrate, or potassium chloride;

[0021] Based on the total mass of the salt solution, the mass percentage content of the salt is 20-30%, for example, it can be 20%, 22%, 24%, 26%, 28%, 30%, and specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0022] Preferably, the salting-out time is 5-48 h, more preferably 10-24 h.

[0023] Preferably, the cleaning is performed by soaking in deionized water for 12-48 hours and then rinsing with running deionized water for 30 minutes.

[0024] The thickness of the MXene-based hydrogel can be adjusted according to actual needs, and can be 1-9 mm, for example, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, and specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0025] Preferably, the solid content of the MXene-based hydrogel is 2%-7%, for example, it can be 2%, 3%, 5%, 7%, and specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range, and it is further preferably 4%-7%.

[0026] In a second aspect, the present invention provides a MXene-based hydrogel material prepared by the above preparation method.

[0027] In a third aspect, the present invention provides the use of the MXene-based hydrogel material with a directional pore structure as described in the second aspect in electromagnetic shielding materials and sensing materials.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The MXene-based hydrogel material provided by the present invention forms a conductive path with MXene and has an internal pore structure with directional arrangement. The high water content provides strong polarization loss, which makes it have excellent electromagnetic shielding performance and can have a shielding effectiveness of more than 50 dB in the X, Ka, K and Ku bands (8.2-40 GHz).

[0030] (2) The MXene-based hydrogel material with directional pore structure has excellent mechanical properties, ultra-flexibility and stretchability, and has wider applications in motion detection.

[0031] (3) The MXene-based hydrogel material provided by the present invention does not require special atmosphere, pressure and temperature, nor does it require complex instruments and equipment. The preparation process is simple, the operating cost is low, and the energy consumption and equipment cost are reduced. In addition, no toxic or harmful substances are produced during the preparation process. The preparation method is environmentally friendly and efficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0033] Figure 1 An optical image of the MXene-based hydrogel material provided in Example 1;

[0034] Figure 2An optical picture showing the flexibility of the MXene-based hydrogel material provided in Example 1;

[0035] Figure 3 A cross-sectional scanning electron microscope image of the MXene-based hydrogel material provided in Example 1;

[0036] Figure 4 A graph showing the test results of the electrical conductivity of the MXene-based hydrogel material provided in Example 2;

[0037] Figure 5 The electromagnetic shielding effectiveness diagram of the MXene-based hydrogel material provided in Example 3;

[0038] Figure 6 A motion detection sensing performance diagram of the MXene-based hydrogel material provided in Example 4;

[0039] Figure 7 A cross-sectional scanning electron microscope image of a MXene-based hydrogel material provided as a comparative example;

[0040] Figure 8 The electromagnetic shielding effectiveness diagram of the MXene-based hydrogel material provided as a comparative example. DETAILED DESCRIPTION

[0041] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0042] Example 1

[0043] A MXene-based hydrogel material having a directional pore structure, wherein the MXene-based hydrogel material is prepared by the following method:

[0044] (1) mixing a MXene aqueous dispersion with a polyvinyl alcohol aqueous solution and dispersing them uniformly so that the mass percentage of MXene in the mixed system is 1% and the mass percentage of polyvinyl alcohol is 4%, thereby obtaining a mixed aqueous dispersion;

[0045] (2) pouring the mixed aqueous dispersion obtained in step (1) into a polytetrafluoroethylene mold and placing it in liquid nitrogen at -196°C for directional freezing;

[0046] (3) The sample obtained in step (2) is placed in a sodium chloride solution, wherein the mass percentage of sodium chloride is 25%, and subjected to salting-out treatment for 24 hours. After washing, a MXene-based hydrogel material having a directional pore structure is obtained.

[0047] The MXene is titanium carbide Ti 3 C2 , which form conductive pathways within the MXene-based hydrogel.

[0048] The optical picture of the MXene-based hydrogel material is as follows Figure 1 As shown, the optical picture of flexibility (bending, curling) is as follows Figure 2 shown.

[0049] The MXene-based hydrogel material was freeze-dried, and the microscopic morphology of the MXene-based hydrogel material provided in this embodiment was tested by scanning electron microscopy (SEM, SU-70, Hitachi). The obtained scanning electron microscope image is as follows: Figure 3 As shown, the MXene-based hydrogel material has a regular and highly oriented pore structure with a pore width of 4–5 μm.

[0050] Example 2

[0051] (1) mixing a MXene aqueous dispersion with a polyvinyl alcohol aqueous solution and dispersing them uniformly so that the mass percentage of MXene in the mixed system is 1.71% and the mass percentage of polyvinyl alcohol is 3%, thereby obtaining a mixed aqueous dispersion;

[0052] (2) pouring the mixed aqueous dispersion obtained in step (1) into a polytetrafluoroethylene mold and placing it in liquid nitrogen at -196°C for directional freezing;

[0053] (3) The sample obtained in step (2) is placed in a sodium acetate solution, wherein the mass percentage of sodium acetate is 20%, and subjected to salting-out treatment for 24 hours. After washing, a MXene-based hydrogel material having a directional pore structure is obtained.

[0054] The MXene-based hydrogel material provided in this embodiment was measured by a four-probe method using a TH26011CS conductivity analysis system. The conductivity test graph obtained is as follows: Figure 4 As shown, the electrical conductivity of the MXene composite film material is 0.43S / m.

[0055] The conductive properties of the MXene-based hydrogel material provided in this embodiment were tested as follows: the MXene-based hydrogel material was connected in series with an LED lamp and a power supply (8V). After the circuit was turned on, the LED lamp emitted light. The conductive properties test results were shown in the figure below. Figure 5 As shown, it is further demonstrated that the MXene-based hydrogel material has good electrical conductivity.

[0056] Example 3

[0057] (1) mixing a MXene aqueous dispersion with a polyvinyl alcohol aqueous solution and dispersing them uniformly so that the mass percentage of MXene in the mixed system is 2.67% and the mass percentage of polyvinyl alcohol is 5%, thereby obtaining a mixed aqueous dispersion;

[0058] (2) pouring the mixed aqueous dispersion obtained in step (1) into a polytetrafluoroethylene mold and placing it in liquid nitrogen at -196°C for directional freezing;

[0059] (3) The sample obtained in step (2) is placed in a sodium sulfate solution, wherein the mass percentage of sodium sulfate is 20%, and subjected to salting-out treatment for 12 hours. After washing, a MXene-based hydrogel material having a directional pore structure is obtained.

[0060] The MXene is titanium carbide Ti 3 C 2 , which forms a conductive pathway in the MXene composite film.

[0061] The electromagnetic shielding performance of the MXene-based hydrogel material provided in this embodiment was measured using a vector network analyzer (VNA, Agilent 8517A). The electromagnetic shielding effectiveness graph obtained is as shown in FIG. Figure 5 As shown, the MXene composite film material can have a shielding effectiveness of more than 50 dB in the X, Ka, K and Ku bands (8.2-40 GHz), and can attenuate electromagnetic waves by more than 99.999%, far exceeding the commercial requirement of 20 dB.

[0062] Example 4

[0063] (1) mixing a MXene aqueous dispersion with a polyvinyl alcohol aqueous solution and dispersing them uniformly so that the mass percentage of MXene in the mixed system is 1.71% and the mass percentage of polyvinyl alcohol is 6%, thereby obtaining a mixed aqueous dispersion;

[0064] (2) pouring the mixed aqueous dispersion obtained in step (1) into a polytetrafluoroethylene mold and placing it in liquid nitrogen at -196°C for directional freezing;

[0065] (3) The sample obtained in step (2) is placed in a sodium chloride solution, wherein the mass percentage of sodium chloride is 30%, and subjected to salting-out treatment for 10 hours. After washing, a MXene-based hydrogel material having a directional pore structure is obtained.

[0066] The MXene is titanium carbide Ti 3 C 2 , which forms a conductive pathway in the MXene composite film.

[0067] The TH26011CS test system was used to measure the resistance change of MXene-based hydrogel materials using the double-probe method to obtain the sensing properties of MXene-based hydrogel materials, such as Figure 6 As shown. Figure 6 (a) It can be seen that when a small deformation (5% stretching) is applied, the MXene-based hydrogel material still detects a change in resistance, which shows that the MXene-based hydrogel material has high sensitivity as an electromechanical sensor. Figure 6 (b) Demonstration of MXene-based hydrogel materials as sensors for finger joint bending. Figure 6 (c) A sensor using MXene-based hydrogel materials to monitor finger tapping is shown, which indicates that MXene-based hydrogel materials can serve as excellent electromechanical sensors for motion detection.

[0068] Comparative Example

[0069] The difference from Example 3 is that in step (2), the cold source is replaced with a refrigerator at -20°C, and the rest remains unchanged to obtain a comparative example. The comparative example is freeze-dried, and a scanning electron microscope (SEM, SU-70, Hitachi) is used to test the microscopic morphology. The obtained scanning electron microscope image is as follows: Figure 7 As shown, a random pore structure is shown, indicating that -20℃ as a cold source cannot construct an outward pore structure;

[0070] The electromagnetic shielding performance of the MXene-based hydrogel material provided in this comparative example was measured using a vector network analyzer (VNA, Agilent 8517A). The electromagnetic shielding effectiveness graph obtained is shown in FIG. Figure 8 As shown, the electromagnetic shielding performance of the comparative example is poorer than that of Example 3. This shows that compared with the random pore structure, the directional pore structure can cause stronger multiple reflections of electromagnetic waves, so that the MXene-based hydrogel material with a directional pore structure has better shielding performance.

[0071] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of them with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. Application of a MXene-based hydrogel material with a directional pore structure in electromagnetic shielding materials and sensing materials, characterized in that: The method for preparing a MXene-based hydrogel material having a directional pore structure comprises the following steps: (1) uniformly dispersing the MXene aqueous dispersion and the water-soluble polymer solution to obtain a mixed aqueous dispersion; (2) pouring the mixed aqueous dispersion obtained in step (1) into a mold and placing it in a cold source for directional freezing; (3) placing the product obtained in step (2) into a salt solution for salting out, and washing to obtain a MXene-based hydrogel material having a directional pore structure; In step (1), based on the mixed aqueous dispersion, the mass percentage of MXene is 0.1% to 10%; based on the mixed aqueous dispersion, the mass percentage of the polymer is 0.1% to 10%; The directional freezing temperature is -196°C.

2. The use according to claim 1, characterized in that: MXene is a two-dimensional transition metal carbide, nitride or carbonitride.

3. The application according to claim 2, characterized in that: The MXene is titanium carbide Ti3C2.

4. The use according to claim 1, characterized in that: The water-soluble polymer includes any one or a combination of at least two of cellulose, hydroxymethyl cellulose, carboxymethyl cellulose, lignin, starch, hydroxymethyl starch, acetic starch, vegetable glue, animal glue, polyacrylamide, polyvinyl pyrrolidone, polyurethane, polyacrylic acid, polyacrylate, polyvinyl alcohol (PVA), polyaniline, polylactic acid, polymaleic anhydride or polyethylene glycol.

5. The application according to claim 4, characterized in that: The water-soluble polymer is polyvinyl alcohol.

6. The use according to claim 1, characterized in that: The mold is a polytetrafluoroethylene mold with a metal bottom.

7. The use according to claim 1, characterized in that: The cold source is liquid nitrogen.

8. The use according to claim 1, characterized in that: The salt includes any one or a combination of at least two of sodium chloride, calcium chloride, copper chloride, sodium citrate, sodium sulfate, sodium nitrate, sodium acetate, potassium sulfate, potassium carbonate, and potassium chloride; Based on the total mass of the salt solution, the mass percentage content of the salt is 20-30%.

9. The use according to claim 8, characterized in that: The salt is any one of sodium chloride, sodium citrate or potassium chloride or a combination of at least two of them.

10. The use according to claim 1, characterized in that: The solid content of the MXene-based hydrogel material with a directional pore structure is 2%-7%.

11. The use according to claim 10, characterized in that: The solid content of the MXene-based hydrogel material with a directional pore structure is 4%-7%.

Citation Information

Patent Citations

  • Muscle-fiber-imitating high-toughness antibacterial healing-promoting hydrogel as well as preparation method and application thereof

    CN114539695A

  • MXene mud composite film as well as preparation method and application thereof

    CN114773655A